Analisis Perhitungan Tingkat Kekumuhan Permukiman di Kabupaten Banjar - Misna Uttri Wiharti (Lambung Mangkurat University Press, 2021)
Slums are settlements that are unfit for habitation due to the irregularity of the building, the high level of building density, and the quality of the buildings and facilities and infrastructure that do not meet the requirements. Banjar Regency is one of the settlements in South Kalimantan Province which has slum areas, namely in Simpang Warga Dalam Village (Aluh-Aluh District), and Muara Halayung Village (Lucky Baru District). In order to improve the quality of slum settlements in Banjar Regency, it is necessary to identify the condition of slums which is an effort to determine the level of slums in a settlement so that the handling of facilities and infrastructure needs can be determined. The identification carried out by analyzing the slum level based on the 2016 PUPR Ministerial Regulation. Implementation is carried out based on the results of survey data, and analysis of the calculation of the slum level scoring assessment. From the results of the analysis, it is known that the classification of the level of slums in Simpang Warga Dalam Village, Aluh-Aluh District is included in the Heavy Slum category, and Muara Halayung Village, Lucky Baru District is included in the Light Slum category.